Single best answer question-writing tips for clinicians. Issue 1096 (1st July 2016) - Walsh, J L; Harris, B H L; Smith, P E
ABSTRACT: Assessment is essential for progression in medical careers. Thus, an important aspect of developing as a clinical teacher is the ability to produce high-quality assessments for junior colleagues. The single best answer (SBA) question format is becoming ubiquitous in the assessment of the application of knowledge in clinical medicine; writing this style of examination question can be a challenge. This concise guide highlights key SBA question-writing tips, aiming to help aspiring clinical teachers set high-quality knowledge assessments.